2015
DOI: 10.3390/catal5010366
|View full text |Cite
|
Sign up to set email alerts
|

B-Site Metal (Pd, Pt, Ag, Cu, Zn, Ni) Promoted La1−xSrxCo1−yFeyO3–δ Perovskite Oxides as Cathodes for IT-SOFCs

Abstract: Perovskite oxides La1−xSrxCo1−yFeyO3-δ (LSCF) have been extensively investigated and developed as cathode materials for intermediate temperature solid oxide fuel cells (IT-SOFCs) due to mixed ionic-electronic conductivity and high electrooxygen reduction activity for oxygen reduction. Recent literature investigations show that cathode performances can be improved by metal surface modification or B-site substitution on LSCF. Although the specific reaction mechanism needs to be further investigated, the promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…[174,175] Improvements were generally more pronounced at lower operational temperatures (500-650 °C) indicating the potential benefit of cathode infiltration with metal promoters for reduced temperature SOFCs. Guo et al [175] pointed out that the effect of metal promoter interaction with the lattice of the oxygen-ion conducting LSCF perovskite could be associated with the size of the metal cation in comparison with that of the A-site or B-site cation in the ABO 3 perovskite. Serra et al [165] experimented with Pd impregnation in LSCF and found by XPS that ≈20% of the Pd is present as metal and the rest exists in oxidized form, presumably incorporated into LSCF B-site.…”
Section: Infiltration Of Noble and Transition Metal Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…[174,175] Improvements were generally more pronounced at lower operational temperatures (500-650 °C) indicating the potential benefit of cathode infiltration with metal promoters for reduced temperature SOFCs. Guo et al [175] pointed out that the effect of metal promoter interaction with the lattice of the oxygen-ion conducting LSCF perovskite could be associated with the size of the metal cation in comparison with that of the A-site or B-site cation in the ABO 3 perovskite. Serra et al [165] experimented with Pd impregnation in LSCF and found by XPS that ≈20% of the Pd is present as metal and the rest exists in oxidized form, presumably incorporated into LSCF B-site.…”
Section: Infiltration Of Noble and Transition Metal Promotersmentioning
confidence: 99%
“…Serra et al [165] experimented with Pd impregnation in LSCF and found by XPS that ≈20% of the Pd is present as metal and the rest exists in oxidized form, presumably incorporated into LSCF B-site. As illustrated by Guo et al [175] the loading level of transitional metal oxides and noble metals has an optimum above which the interfacial oxygen transfer can be negatively influenced as the promoting nanoparticles start to obstruct the interaction sites of interfacial O with the cathode surface oxygen vacancies (see Figure 10). Sakito et al [168] reported enhancement of maximum output power density by 1.5 times by infiltration of AgNO 3 solutions into porous La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 electrodes.…”
Section: Infiltration Of Noble and Transition Metal Promotersmentioning
confidence: 99%
“…Herein, we introduce three types of infiltrates (Co, Cu and CeO 2 ). It is expected that the addition of Co and Cu can enhance the catalytic activity and carbon resistance, respectively . CeO 2 not only can increase the redox and thermal stabilities of the infiltrated Co or Cu, but also behave as an oxygen reservoir to enhance the carbon resistance of the anode.…”
Section: Introductionmentioning
confidence: 99%
“…Several detailed review papers have been published summarising some exceptionally encouraging results [6,8,[12][13][14][15][16][17][18]. The infiltrated inks were usually calcined at relatively low temperature, typically below 800°C, resulting in formation of distributed nanoparticles without detrimental chemical reaction between the scaffold and the infiltrate material.…”
Section: Introductionmentioning
confidence: 99%